Handbook of Japanese syntax - Shibatani, Masayoshi; Miyagawa, Shigeru; Noda, Hisashi (Handbooks of Japanese language and linguistics., 2017)
Studies of Japanese syntax have played a central role in the long history of Japanese linguistics spanning more than 250 years in Japan and abroad. More recently, Japanese has been among the languages most intensely studied within modern linguistic theories such as Generative Grammar and Cognitive/Functional Linguistics over the past fifty years. This volume presents a comprehensive survey of Japanese syntax from these three research strands, namely studies based on the traditional research methods developed in Japan, those from broader functional perspectives, and those couched in the generative linguistics framework. The twenty-four studies contained in this volume are characterized by a detailed analysis of a grammatical phenomenon with broader implications to general linguistics, making the volume attractive to both specialists of Japanese and those interested in learning about the impact of Japanese syntax to the general study of language. Each chapter is authored by a leading authority on the topic. Broad issues covered include sentence types (declarative, imperative, etc.) and their interactions with grammatical verbal categories (modality, polarity, politeness, etc.), grammatical relations (topic, subject, etc.), transitivity, nominalizations, grammaticalization, word order (subject, scrambling, numeral quantifier, configurationality), case marking (ga/no conversion, morphology and syntax), modification (adjectives, relative clause), and structure and interpretation (modality, negation, prosody, ellipsis).